RSSI and Public Key Infrastructure based Secure Communication in Autonomous Vehicular Networks - Balan, K.; Adnan Shahid, Khan; Azlina, Binti Ahmadi Julaihi; Seleviawati, Binti Tarmizi; Pillay, K. S.; Abdulrazak, L. F.; H., Sallehudin (The Science and Information (SAI) Organization Ltd., 2018)
—Autonomous Vehicular Ad hoc Networks (AVANET) is also known as intelligent transportation systems. AVANET ensures timely and accurate communications between vehicle to vehicle and Vehicle to Roadside Unit (RSU) to improve road safety and enhance the efficiency of traffic flow. Due to open wireless boundary and high mobility, A-VANET is vulnerable to several security threats especially impersonation, denial of service, pollution attacks. This paper presents a novel Received Signal Strength Indicator (RSSI) based public key infrastructure (PKI) to address the above-mentioned attacks. Each incoming signal will be authenticated based on RSSI value and digital signal (obtained using PKI) is utilized for cryptography and communication within the insecure channel. The proposed solution is verified with and without the presence of attacker by evaluating the packet delivery ratio and packet overhead.